The association between treatment and systemic inflammation in acromegaly. (April 2021) - Wolters, T.L.C.; van der Heijden, C.D.C.C.; Pinzariu, O.; Hijmans-Kersten, B.T.P.; Jacobs, C.; Kaffa, C.; Hoischen, A.; Netea, M.G.; Smit, J.W.A.; Thijssen, D.H.J.; Georgescu, C.E.; Riksen, N.P.; et al.
Abstract: Objective: Acromegaly is characterized by an excess of growth hormone (GH) and insulin like growth-factor 1 (IGF1), and it is strongly associated with cardiovascular diseases (CVD). Both acute and long-lasting pro-inflammatory effects have been attributed to IGF1. Previous results suggest the presence of systemic inflammation in treated patients. Here we assessed the association between treatment of acromegaly, systemic inflammation and vascular function. Design: Ex vivo cytokine production and circulating inflammatory markers were assessed in peripheral blood from treated and untreated acromegaly patients ( N  =  120 ), and compared them with healthy controls. A more comprehensive prospective inflammatory and vascular assessment was conducted in a subgroup of six treatment-naive patients with follow-up during treatment. Results: Circulating concentrations of VCAM1, E -selectin and MMP2 were higher in patients with uncontrolled disease, whereas the concentrations of IL18 were lower. In stimulated whole blood, cytokine production was skewed towards a more pro-inflammatory profile in patients, especially those with untreated disease. Prospective vascular measurements in untreated patients showed improvement of endothelial function during treatment. Conclusions: Acromegaly patients are characterized by a pro-inflammatory phenotype, most pronounced in those with uncontrolled disease. Treatment only partially reverses this pro-inflammatory bias. These findings suggest that systemic inflammation could contribute to the increased risk of CVD in acromegaly patients. Highlights: Acromegaly patients are characterized by a pro-inflammatory phenotype. This phenotype is most pronounced in those with uncontrolled disease. Treatment only partially reverses this pro-inflammatory phenotype. Systemic inflammation could contribute to the increased risk of CVD in acromegaly.